ChemInform Abstract: Preparation and Doping Mode of Doped LiMn2O4 for Li‐Ion Batteries. Issue 5 (4th February 2014) - Liu, Qiuling; Wang, Shengping; Tan, Haibo; Yang, Zhigao; Zeng, Jian
Abstract Review: 94 refs.